PENUAAN POPULASI DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI MAKRO JANGKA PANJANG DI ASIA TIMUR - Muhammad Taali; Triana Prihatinta; Ardila Prihadyatama (LPPM Politeknik Pratama, 2021)
This study will examine the impact of the population aging phenomenon on innovation and long-term macroeconomic balance in several East Asian countries. The variables used in this study include the number of elderly population, population growth, income per capita, birth rate, death rate, institutional quality, education level, unemployment rate and gross national expenditure. The data analysis method that will be used is the Monash-China Hunan-University General Equilibrium (MC-HUGE) model which is the development of the Computable General Equilibrium (CGE) model. The MC-HUGE model is built on the Walrasian general equilibrium theory and input-output theory, including the three main elements in production activities, namely land, capital and labor.